Učne težave z vidika učiteljev v osnovni šoli - Drofenik, Petra (Revija za elementarno izobraževanje, 2010)
Teachers' views of learning difficulties in primary school. The paper presents a discussion on the appearance of learning difficulties, which are present among very heterogeneous group of pupils in Slovene elementary schools. The research was based on empirical facts collected in nineteen different schools. We focused our attention on teachers, as a part of the school system. We were interested in their opinions and experience about the field of research. The topics covered were as follows: identifying learning difficulties, form aid, coordination and planning work, specialties and cooperation with parents and others in an elementary school. Learning difficulties are mostly the consequence of various intermingling factors. They are present in very heterogeneous group of pupils with different cognitive, social, emotional (among other) factors, which are then amplified by other pupils. Pupils with learning difficulties need special education but they often have more or less interaction with a school before the process of teaching and learning begins.